Psychosocial Support: a path for improving refugees’ mental health and cross-cultural adaptability - Moreno, Anna Carolina; Francischetti, Ieda (Advances in Social Sciences Research Journal, 2021)
This article aims at analysing how psychosocial support (PSS) projects focused on refugees' mental health might contribute to improving their well-being and resilience in camps or during resettlement. Their journeys usually cause an increase in individuals’ mental health instability, not only related to trauma but also because they require the capability of adjusting to different realities and cultures. This paper works toward answering the question of how PSS potentially capacitates refugees to continuously adapt to new environments through exploratory research of qualitative nature.